A systematic literature review on the use of vacuum assisted closure for enterocutaneous fistula. (September 2016) - Misky, A.; Hotouras, A.; Ribas, Y.; Ramar, S.; Bhan, C.
Abstract: Aim: Enterocutaneous fistula (ECF) is considered to be one of the most challenging complications a general surgeon can encounter. The current mainstay of treatment is surgical closure, associated with significant morbidity and mortality. Vacuum assisted closure (VAC) has been successfully used for closure of persistent abdominal wounds for a number of years. This study aims to investigate whether current literature supports the use of VAC for ECF. Method: A PubMed search of the search terms 'enterocutaneous fistula' and 'vacuum assisted closure/therapy' was performed in December 2014. Results were restricted to articles involving human subjects with an available abstract and full text written between 1950 and 2014. The end‐points analysed included rate of fistula closure, duration of follow‐up, and morbidity and mortality where available. Results: Ten studies (all level IV) including 151 patients were examined. In all except one, surgery was the underlying aetiology with median number of fistulae per patient of one. The median rate of closure with VAC was 64.6% (7.7–100%) with healing occurring within 58 (12–90) days. Follow‐up was only mentioned in three of the 10 studies, in which the patients were followed for 3, 20 and 28.5 months. No complications were reported in all but one of the studies, in which abdominal wall disruption and intestinal obstruction were identified in a minority of patients. Conclusion: The included studies suggest that VAC therapy may be considered a safe treatment for ECF. The current evidence is generally of low level and characterized by heterogeneity. Definitive recommendations based on this information cannot therefore be made. Further studies are necessary to establish any proven benefit over standard surgical or conservative therapy.